A review on China's wind power accommodation in the background of "Internet+" strategy. (16th November 2017) - Hou, Jianchao; Zhai, Xiaolong; Liu, Pingkuo
Summary: The consumption of fossil fuel has resulted in global warming, environmental pollution, and many other crucial problems. Replacing fossil fuel with renewable energy has become an important issue over the recent decades. As a renewable clean energy, wind power is a relatively well‐developed and promising energy method for current technology development in China. Under the background of growing demand for electricity and enhancing awareness for environmental, the "Internet+ wind power" concept has emerged based on both the wind power's characteristics that renewable and non‐polluting, and the rapid development of the Internet in China. Through querying an amount of literature and information, this paper reveals the resource endowment and policy environment about wind power and energy Internet at first. Then, the PEST‐SWOT strategy analysis model is used to analyze the internalities (strengths and weaknesses) and the externalities (opportunities and threats) of "Internet+ wind power". According to these results, the paper puts forward some measures (development and utilization, business mode) for wind power accommodation. Then some policy recommendations have been proposed. The government should provide favorable conditions for wind power grid with the "Internet+" technology innovation. Abstract :